Exon 10 polymorphism of the GHR|CviAII gene and its association with growth traits in Bali cattle - TAPAUL ROZI; MASKUR MASKUR; NI PUTU SARINI; WAYAN SUARDANA (Society for Indonesian Biodiversity, 2025)
Abstract. Rozi T, Maskur, Sarini NP, Suardana W. 2025. Exon 10 polymorphism of the GHR|CviAII gene and its association with growth traits in Bali cattle. Biodiversitas 26: 6039-6046. Bali cattle (Bos javanicus) are an important local genetic resource that supports beef production in eastern Indonesia, particularly under smallholder communal breeding systems on Lombok Island. Growth traits in this breed are influenced by both management practices and variation in candidate genes such as the Growth Hormone Receptor (GHR). This study aimed to identify exon 10 polymorphisms of the GHR gene using the CviAII restriction enzyme and to analyze their relationship with major growth traits in Bali cattle. A total of 203 animals, consisting of 106 males and 97 females, were evaluated using Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) and the General Linear Model (GLM). Sequencing detecteded a new synonymous mutation, g.1777T>C, which produced two genotypes, CT and TT, with no CC genotype detected. The T allele showed a higher frequency in both sexes, and observed heterozygosity was higher than expected, indicating heterozygote excess under group-based breeding and sire rotation. Association analysis showed that the CT genotype was linked to superior growth performance compared with TT. In males, CT individuals had a birth weight of 17.22±1.17 kg and a yearling weight of 142.18±6.57 kg, compared with 16.56±1.18 kg and 133.96±5.82 kg for TT. In females, CT individuals had a birth weight of 15.71±0.82 kg and a yearling weight of 133.87±6.18 kg, compared with 15.06±1.10 kg and 126.89±5.26 kg for TT. Weaning weight did not differ among genotypes, suggesting a stronger influence of maternal and management factors. The polymorphic information content indicated moderate informativeness and the need for further validation. These results support the potential of the GHR|CviAII locus as a complementary molecular marker for growth-based selection in Bali cattle.